DOI: 10.31274/rtd-180813-14898
|View full text |Cite
|
Sign up to set email alerts
|

The combining ability of selected alfalfa clones as related to the self-fertility of the clones, their F1 and F2 progenies

Abstract: The quality of this reproduction is dependent upon the quality of the copy submitted. Broken or indistinct print, colored or poor quality illustrations and photographs, print bleed-through, substandard margins, and improper alignment can adversely affect reproduction. In the unlikely event that the author did not send a complete manuscript and there are missing pages, these will be noted. Also, if unauthorized copyright material had to be removed, a note will indicate the deletion. UMI UMI Microform DP12493

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
9
0

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 0 publications
6
9
0
Order By: Relevance
“…This may be evidenced from the cor relation studies made, which show that self-fertility of the S-^ plants is positively associated with average backcrossand sib-fertility. A positive relationship between self-and cross-fertility has previously been shown by McAllister (1950) and Bolton (1948). Such significant correlations would un likely be brought about by the operation of the S incompatibil ity gene systems.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…This may be evidenced from the cor relation studies made, which show that self-fertility of the S-^ plants is positively associated with average backcrossand sib-fertility. A positive relationship between self-and cross-fertility has previously been shown by McAllister (1950) and Bolton (1948). Such significant correlations would un likely be brought about by the operation of the S incompatibil ity gene systems.…”
Section: Discussionsupporting
confidence: 63%
“…Koffman (1959) found that selfed progenies yielded only 55 to 75 per cent of the forage yield of non-inbred parental clones. Similar results were obtained by McAllister (1950). Bolton (1948) showed that progenies of crosses among second generation selfed plants derived from the same parents were intermediate in seed and forage yield between comparable inbred lines and outcross progenies.…”
Section: Inbreeding In Alfalfasupporting
confidence: 69%
See 1 more Smart Citation
“…McALLISTER (1951) found a positive correlation between yields of parental clones and yields of their h and Fl progenies . DAvis (1953), in a wide discussion of the subject, observed that the difference between polycross progenies with the highest and lowest yield was half that observed between the best and the poorest f, progeny .…”
Section: Review Of Literaturementioning
confidence: 96%
“…Similarly, Wilsie (1958) found self-fertility values of 437 alfalfa hybrids from first-generation single-and 3-way crosses were strongly skewed, Wilsie and Skory (1948) observed a range in selffertility from 0.24 to 2.23 seeds per tripped flower among alfalfa clones, and Wilsie (I95I) reported a range of selffertility from 0.12 to 1.84 seeds per tripped flower. Studies by McAllister (1950), Koffman (1959) and Williams (1964) showed remarkably wide ranges in self-fertility, also. San dal (1946) found 0.15 seeds and 1.25 seeds per flower, re spectively, for low and high-fertility groups of clonal lines.…”
Section: Review Op Literaturementioning
confidence: 99%